Mycobacteriophages and Their Applications - Andrea Bonacorsi; Caterina Ferretti; Mariagrazia Di Luca; Laura Rindi (MDPI AG, 2024)
Mycobacterial infections caused by tuberculous and non-tuberculous strains pose significant treatment challenges, especially among immunocompromised patients. Conventional antibiotic therapies often fail due to bacterial resistance, highlighting the need for alternative therapeutic strategies. Mycobacteriophages are emerging as promising candidates for the treatment of mycobacteria. This review comprehensively explores phage isolation, characterization, and clinical applications. Despite the need for more extensive in vitro and in vivo studies, existing evidence shows their efficacy against both sensitive and antibiotic-resistant mycobacterial strains, even under disease-mimicking conditions, particularly when used in cocktails to minimize resistance development. Mycobacteriophages can be engineered and evolved to overcome limitations associated with lysogeny and narrow host range. Furthermore, they exhibit activity in ex vivo and in vivo infection models, successfully targeting mycobacteria residing within macrophages. Delivery methods such as bacterial and liposomal vectors facilitate their entry into human cells. Considering the potential for phage-treatment-induced bacterial resistance, as described in this review, the combination of mycobacteriophages with antibiotics shows efficacy in countering mycobacterial growth, both in the laboratory setting and in animal models. Interestingly, phage-encoded products can potentiate the activity of relevant antibiotics. Finally, the application of phages in different compassionate cases is reported. The positive outcomes indicate that phage therapy represents a promising solution for the treatment of antibiotic-resistant mycobacteria.